Ingredients and Technical Parameters of a New Type of Semi-Finished Meat Containing Dutch Cabbages - Dashtoyan, Anna; Baluyants, Yana; Hovsepyan, Lilit (ՀԱԱՀ հիմնադրամ)
Increasing demand for semi-finished meat has led manufacturers to increase production volumes, renewing and modernizing their assortments in parallel. Technologies and recipes for semi-finished products production are known, in which animal and vegetable raw materials are combined. In addition, it contributes to the rational use of raw materials, the provision of quality food, and the improvement of technical and economic indicators. As a dietary raw material, white cabbage is an effective raw material to use in the production of semi-finished products.
Keywords: Food Science and Technology